PENGUATAN KAPASITAS IBU PKK DALAM MENGEMBANGKAN USAHA RUMAH TANGGA MELALUI EDUKASI BISNIS DAN DIGITAL MARKETING - Putri Salsabila; Annisa Fadhilla Ahmad; Khairani Elfina; Elsa Defri Yani; Cindy Fatikasari; Fajar Alfrigo; Hesti Hanifa; Mhd Ilval Hakim; Revita Maharani; Tasya Defri Pratama Putri; Syauvy Husnainy; Yulia Ningsih (ASOSIASI IDEBAHASA KEPRI, 2026)
The development of digital technology has brought progress to the general public because it can support the community's economy. However, a lack of digital literacy is also a hindering factor, especially among women in the Family Welfare Movement (PKK). Therefore, this community service activity aims to educate PKK women about business and digital marketing. The tools used included Shopee, Canva, WhatsApp, Instagram, and Facebook. The community service activity was carried out using brainstorming, lectures, discussions, and mentoring methods. Lectures and brainstorming methods were used to explain the material and practice of using digital marketing applications. The discussion and mentoring methods are expected to produce PKK women who understand business and digital marketing and are able to empower their families economically. This article also aims to analyze the importance of strengthening the capacity of PKK women through business and digital marketing education as a strategy for family economic empowerment. The methods used were a literature review and analysis of online information discussing the empowerment of PKK women. The analysis showed that education can improve the marketing knowledge and skills of PKK women. The use of social media and ecommerce has been proven to help expand digital market reach, improve products, and boost the family economy.